2010
DOI: 10.1128/aac.00017-09
|View full text |Cite
|
Sign up to set email alerts
|

Novel VIM Metallo-β-Lactamase Variant from Clinical Isolates of Enterobacteriaceae from Algeria

Abstract: Five different strains of bacteria belonging to the family Enterobacteriaceae were isolated from two patients hospitalized in the intensive care unit of the Central Military Hospital of Algiers, Algeria. All five strains, one Providencia stuartii strain, two Escherichia coli strains, and two Klebsiella pneumoniae strains, were intermediate or resistant to all beta-lactams, including carbapenems. Synergy between imipenem and EDTA was observed for all five strains. The results of the PCR experiment confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
(35 reference statements)
0
35
0
1
Order By: Relevance
“…Because benzylpenicillin and ampicillin differ only by an amino group on the C-6 side chain, the position of the flapping loop in a narrow conformation for VIM-4 could explain this behavior. VIM-19, another VIM-1 variant, possesses two substitutions (S228R and N215K) (38). Its catalytic efficiency toward benzylpenicillin and meropenem was similar to that of VIM-4 (Table 3) (39).…”
Section: Discussionmentioning
confidence: 94%
“…Because benzylpenicillin and ampicillin differ only by an amino group on the C-6 side chain, the position of the flapping loop in a narrow conformation for VIM-4 could explain this behavior. VIM-19, another VIM-1 variant, possesses two substitutions (S228R and N215K) (38). Its catalytic efficiency toward benzylpenicillin and meropenem was similar to that of VIM-4 (Table 3) (39).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to other countries, where the bla NDM gene has been identified mainly in Enterobacteriaceae, the bla NDM gene has been reported only in A. baumannii clinical isolates from Algeria (3, 7). However, other types of carbapenemase-acquiring isolates have been reported in Algeria, such as bla VIM in Enterobacteriaceae (8) and P. aeruginosa (9). The bla OXA-24 , bla OXA-23 , and bla OXA-58 genes have been also reported in Annaba and Tlemcen, Algeria (3, 10, 11).…”
mentioning
confidence: 99%
“…MIC analysis showed that HSG398-V01 was more active than HSG398-DH5␣ against imipenem and ceftazidime, with 4-and 8-fold increases, respectively (Table 1), which suggested that this bla gene is functional in the three P. putida isolates. Phenotypic detection of metallo-␤-lactamases was performed on the three P. putida isolates according to the previous report (22), and synergy between imipenem and EDTA was observed for all three strains (data not shown).…”
mentioning
confidence: 99%